Rwandan Women in Higher Education: Progress, Successes, and Challenges - Reilly, Elizabeth C. (Frontiers in Education, 2021)
In nearly three decades since Rwanda’s genocide and civil war, its education sector has undergone reconstruction to an unprecedented degree within higher education. While greater numbers of girls are attending university, and more women are becoming university faculty members, their status in educational leadership roles remains unclear. This qualitative investigation sought to present insight into four women who serve as professors and executive leaders within the higher education system by examining their progress, successes, and challenges. Four of the many insights that have emerged include women’s smaller acceptance rate into higher education as undergraduates; the country’s lack of Ph.D. programs, thereby requiring women to leave the country in order to obtain the terminal degree; disproportionate service expectations placed on women academics as compared to men that affect scholarly output; and society’s expectation for women’s responsibilities as wives and mothers regardless of career responsibilities or status. To remedy these findings, further investigation can shed light on the reasons for low acceptance of women into the university; may lead to development of a strategic plan to address the lack of opportunities for students to enter graduate level education leading to the Ph.D.; and may address broader national policies that support women academics such as attention to child care and mentoring for promotion.